2021
DOI: 10.5194/cp-17-2091-2021
|View full text |Cite
|
Sign up to set email alerts
|

Climate, cryosphere and carbon cycle controls on Southeast Atlantic orbital-scale carbonate deposition since the Oligocene (30–0 Ma)

Abstract: Abstract. The evolution of the Cenozoic cryosphere from unipolar to bipolar over the past 30 million years (Myr) is broadly known. Highly resolved records of carbonate (CaCO3) content provide insight into the evolution of regional and global climate, cryosphere, and carbon cycle dynamics. Here, we generate the first Southeast Atlantic CaCO3 content record spanning the last 30 Myr, derived from X-ray fluorescence (XRF) ln(Ca / Fe) data collected at Ocean Drilling Program Site 1264 (Walvis Ridge, SE Atlantic Oce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 128 publications
0
26
0
Order By: Relevance
“…Increases in the MAR of biogenic components (CaCO 3 , opal, organic carbon, phosphorus) between ∼ 9 and 4 Ma have been measured in sediments from the Pacific, Indian, and Atlantic Oceans (Farrell et al, 1995;Lyle and Baldauf, 2015;Van Andel et al, 1975;Grant and Dickens, 2002;Delaney and Filippelli, 1994;Hermoyian and Owen, 2001;Dickens and Owen, 1999;Drury et al, 2021). This period of increased biogenic sedimentation, supported by independent paleoproductivity proxies (e.g.…”
Section: Late Miocene Sedimentation Patterns In the Southern Bay Of B...mentioning
confidence: 84%
See 1 more Smart Citation
“…Increases in the MAR of biogenic components (CaCO 3 , opal, organic carbon, phosphorus) between ∼ 9 and 4 Ma have been measured in sediments from the Pacific, Indian, and Atlantic Oceans (Farrell et al, 1995;Lyle and Baldauf, 2015;Van Andel et al, 1975;Grant and Dickens, 2002;Delaney and Filippelli, 1994;Hermoyian and Owen, 2001;Dickens and Owen, 1999;Drury et al, 2021). This period of increased biogenic sedimentation, supported by independent paleoproductivity proxies (e.g.…”
Section: Late Miocene Sedimentation Patterns In the Southern Bay Of B...mentioning
confidence: 84%
“…S4b). A 405 kyr modulation of the ocean carbon cycle, primarily recorded in carbonate content and benthic δ 13 C records (Herbert, 1997;Drury et al, 2021;De Vleeschouwer et al, 2020;Westerhold et al, 2020;Pälike et al, 2012;Paillard, 2017;Holbourn et al, 2007) but also in productivity and monsoon-related dust records (Rickaby et al, 2007;Wang et al, 2010), has been observed throughout the Cenozoic and Mesozoic sedimentary record. In middle Miocene records, poor carbonate preservation noted during eccentricity maxima is interpreted in terms of transient shoaling of the carbonate saturation horizon (Holbourn et al, 2007;Flower and Kennett, 1994).…”
Section: Orbital Forcing Of Late Miocene South Asian Summer Monsoon W...mentioning
confidence: 99%
“…Obliquity cycles are also identified in the ODP Site 1146 Mg/Ca-SST record from the South China Sea, with a similar increase in power after 7.5 Ma (Figure S8 in Supporting Information S1; Holbourn et al, 2018). The direct effect of obliquity on low-latitude insolation is small, and the appearance of strong obliquity cycles in tropical SSTs is broadly concurrent with their appearance in benthic δ 13 C and δ 18 O from Site U1443 (Bolton et al, 2022) and in a late Miocene benthic δ 18 O global stack (Drury et al, 2021), suggesting an increase in tropical SST sensitivity to obliquity linked to an increase in high-latitude forcing. Cross-wavelet analysis of SST and benthic δ 18 O from Site U1443 show high coherency (>95%) in the obliquity band (Figure 3e), suggesting that SSTs and deep-ocean δ 18 O (linked to continental ice volume and temperature in deepwater formation regions) were coupled on orbital timescales during the late Miocene.…”
Section: Drivers Of Tropical Indian Ocean Sst Variability On Orbital ...mentioning
confidence: 79%
“…However, the benthic oxygen isotope record also indicates an earlier decreasing δ 18 O trend between ~19.5 Ma and ~17 Ma (Figure 7; De Vleeschouwer et al, 2017;Westerhold et al, 2020 ) which is correlatable with an Early Miocene warming trend from ~20 Ma as indicated by Mg/Ca temperature proxy (Cramer et al, 2011). Widespread decreases in deep ocean CaCO3 mass accumulation rates have also been used to argue for increasing oceanic dissolved inorganic carbon (DIC) concentrations during this interval, suggesting that the gradual warming was caused by changes in the global carbon cycle (Drury et al, 2021). We note a step increase in chert horizons in the global oceanic records, starting around 19 Ma and terminating around 13 Ma (Muttoni & Kent, 2007).…”
Section: Accepted Articlementioning
confidence: 97%